ANALYSIS OF THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE - Akbar, Yunata Kandhias (CENTRAL ASIA AND THE CAUCASUS, 2022)
This paper has a purpose to know the connection between two variables which is independent variables (Organizational Commitment, Motivation and Compensation) and dependent variable (Employee Performance) at Technical Division PT Advance Digital. The methodology that is used in this research is using multiple linear regression, T-test and F-test. According to the results, the effect of Organizational Commitment, Motivation and Compensation on the Performance of Technical Division in PT Advance Digital, as already predicted, Organizational Commitment, Motivation and Compensation are affecting the Performance of Employees. From the three variables, it was found that motivation has the most dominant effect on the performance of employees.